The Effect of Workload and Work Stress on Employee Per-formance at the Regional Revenue Agency of Sikka Regency - Yoseph Henrikus; Maria Silvana Mariabel Carcia; Vinsensius Ama Muda (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The background of this research aimed to: (1) determine the description of employee performance, workload, and work stress; (2) analyze the influence of Workload and Job Stress on employee performance both partially and simultaneously.The population in this research were employees of the Sikka Regency Regional Revenue Agency, totaling 61 people. This research was carried out with a sanmpling technique or saturated sampling (total sampling). Data was collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing is carried out through the F-test and t-test.The results of the descriptive analysis showed that the employee performance. Work Load and Work Stress variables were categorized as good. The statistical results of the t-test showed that the Workload variable had a positive and insignificant effect on employee performance. Furthermore, the Job Stress variable has a positive and significant effect on employee performance. The statistical results of the F test showed that simultaneously the variables Workload and Job Stress had a significant effect on employee performance. The results of the determination analysis showed that the two independent variables in this research were able to explain the fluctuation ofemplovee performance of the Regional Revenue Agency of Sikka Regency by 12.5%.